2016
DOI: 10.1108/maj-12-2015-1293
|View full text |Cite
|
Sign up to set email alerts
|

Audit committee and integrated reporting practice: does internal assurance matter?

Abstract: Purpose This paper aims to examine the role of the audit committee function as an internal assurance provider in the emerging integrated reporting (IR) practice. In particular, the authors examine the role of the overall effectiveness, as well as specific aspects, of the audit committee function in IR practice. Design/methodology/approach The authors examine the integrated reports of 246 firm-year observations of large South African companies over a three-year period (2011-2013), following the introduction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
4
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 41 publications
4
49
4
1
Order By: Relevance
“…In addition, various AC‐related variables are included as control variables (Ahmed Haji, Ahmed Haji, Anifowose, & Anifowose, ; Li et al, ): size, independence, and tenure. AC size (ACSIZE) refers to the total number of members on the committee.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, various AC‐related variables are included as control variables (Ahmed Haji, Ahmed Haji, Anifowose, & Anifowose, ; Li et al, ): size, independence, and tenure. AC size (ACSIZE) refers to the total number of members on the committee.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, Gerwanski et al () found a positive relationship between gender diversity and materiality disclosure quality. Regarding the role of the audit committee, Velte () highlighted how the expertise of the latter improves the readability of the integrated reports, and, similarly, Ahmed Haji and Anifowose () found that both the effectiveness and the authority of the audit committee and the number of meetings encourage the inclusion of more information in integrated reports and increase the level of compliance with the IIRC framework. Finally, Ahmed Haji and Anifowose () highlighted how the presence of a sustainability committee increases the amount of information in the integrated reports and the level of alignment with IIRC principles.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We are not saying that non-financial information is inherently inaccurate, but companies will have to improve their internal controls over non-financial information flows and professionalize their information systems so that auditors can test them and rely on their controls [5]. Audit committees and other systems of corporate governance will play a key role [50,51], but they are not a focal point of this study.…”
Section: Assurance On Integrated Reportingmentioning
confidence: 99%